Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1094/mpmi-09-15-0200-r
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Plant Cell Death–Inducing Secreted Proteins From Ustilaginoidea virens

Abstract: Ustilaginoidea virens (Cooke) Takah (telemorph Villosiclava virens) is an ascomycetous fungus that causes rice false smut, one of the most important rice diseases. Fungal effectors often play essential roles in host-pathogen coevolutionary interactions. However, little is known about the functions of U. virens effectors. Here, we performed functional studies on putative effectors in U. virens and demonstrated that 13 of 119 putative effectors caused necrosis or necrosis-like phenotypes in Nicotiana benthamiana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 61 publications
6
92
0
Order By: Relevance
“…2) but also for its cell death–inducing activity (Fig. 3) 15, 33, 34 . We found that cell death was only observable with PstSCR1-FLAG when expressed in the strong pTRBO vector.…”
Section: Resultsmentioning
confidence: 99%
“…2) but also for its cell death–inducing activity (Fig. 3) 15, 33, 34 . We found that cell death was only observable with PstSCR1-FLAG when expressed in the strong pTRBO vector.…”
Section: Resultsmentioning
confidence: 99%
“…It was predicted that UV_2799 encodes a putative secreted cysteine‐rich effector (named thereafter SCRE1) in U. virens (Zhang et al ., ) . We first used a yeast secretion system to verify the functionality of the SCRE1 signal peptide (Fang et al , ; Jacobs et al ., ). The predicted signal peptide‐encoding sequence of SCRE1 was fused in frame with a truncated SUC2 gene that encodes invertase but lacks its own signal peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Effectors play essential roles in fungal virulence (Lo Presti et al , ; Oliveira‐Garcia and Valent, ). However, despite genomics‐based predictions, few effectors have been functionally characterized in U. virens (Fang et al , ). In this study, we identified an essential virulence effector, SCRE1, in U. virens and provided evidence that this effector suppresses rice immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations